A Challenging Case of Recurrent Ogilvie Syndrome: Exploring Causes and Treatment Modalities - Ahmad Alnasarat; Mostafa Elrazzaz; Nouraldeen Manasrah (Case Reports in Gastrointestinal Medicine)
Conclusion: This challenging case highlights the complexities of managing Ogilvie syndrome and the importance of early identification and a stepwise approach to treatment. Incorporating a patient-centered plan utilizing conservative measures, pharmacological agents and endoscopic interventions are essential for improving outcomes in these cases.